Middle to late Holocene palaeoenvironmental study of Gialova Lagoon, SW Peloponnese, Greece. (20th May 2018) - Emmanouilidis, Alexandros; Katrantsiotis, Christos; Norström, Elin; Risberg, Jan; Kylander, Malin; Sheik, Taariq Ali; Iliopoulos, George; Avramidis, Pavlos
Abstract: The coastal areas of Eastern Mediterranean have long been the subject of research, due to their rapid geomorphological changes, but also because of their archaeological interest. Our study is focused on a shallow coastal lagoon of Peloponnese, Gialova Lagoon, which for several years has attracted the scientific interest of archaeologists, geomorphologists as well as sedimentologists. Gialova lagoon is located near the ancient city of Pylos, the kingdom of king Nestor during the Mycenaean period (1600–1100 BC). The objectives of this study are: (a) to reconstruct the middle to late Holocene depositional environments of the lagoon and (b) to correlate our data to already existing publications, in order to shed new light on the Holocene evolution of the lagoon and the associated coastal palaeoenvironmental changes. An 8 m deep vibracore was drilled and a multi proxy analysis was carried out on the sediment sequence, including sedimentological (grain size analysis and moment measures, total organic carbon – TOC, total nitrogen – TN and total phosphorus – TP), high resolution geochemical (XRF-scanning) and palaeontological (micro- and macro faunal) analysis. The chronological framework is based on five 14 C datings forming the basis for an age depth model, calculated using the OxCal software. The radiocarbon dates from previous studies (6 cores, ∼20 dates) were also taken into account. The data synthesis and interpretation provided robust and coherent indications regarding the palaeoenvironment, shoreline changes and the rate of geomorphological changes of the coastal area of Gialova Lagoon, as well as useful information about the palaeonvironmental and palaeoclimatic conditions that prevailed during the Mycenaean period. The interpretation, reveal a transition from a shallow marine environment (6500-5800 yr B.P.) to a brackish/lagoonal (5800-3300 yr B.P.), followed by a shift towards a freshwater/marsh environment (3300 yr B.P. to present).